L’ENSEIGNEIMENT A DISTANCE PAR TELEVISION DANS LE CONTEXTE DU COVID-19. CAS DES ECOLES DE LA VILLE DE BUKAVU EN REPUBLIQUE DEMOCRATIQUE DU CONGO. CONSEILS PRATIQUES AUX USAGERS. - Bienvenu, KASIMU IDI (IJRDO- Journal of Educational Research, 2024)
The self-managementand the autonomy of learnerss mustbe taken into accountWhendeveloping plansdistance and teaching learning todistance.Before COVID-19, learningprograms distance targeted mainadult learnerscompetentself-management or young peoplelearnings with daccompanying persons. During theCovid-19, however, the appTarget distanceretentionhasPPrevents at all stages.Programs to APPROGDistance homehave multiple dEFISto students with regard toconcerns their habits oflearning and their masteryself, theirmotivation, leuRS Relations with their parentsas well as their projects ofcome. The fact thatthe routinesdailydisturbed, in particular, canrequirein place rigorous hoursseparated foreachactivity and often generatea pace of learningslower. Electronicselectronic(telephonemobile, television etc.),require self-control skills that students may not haveRAcquired. For students to remain involvedS sans the presence of teachers, theycount potenonparents formotivate them and manage yourNT that badly their activitieslearning, whichcancause tensionin famil relationshipsiales. In addition, according to the age of the learners,the incrementTudging of the situation in hisTogether can causeanxietyAs for the passage inthe upper class.On the other hand, study at homeby means of televisionoffers agoodopportunity to learnerss d'Improve their skills inself-management. Comprehealth andCOVID19 security, become an autonomous personand active and ensure his IBEN-being can be partofskills to acquire, dyears the framework of learningthroughout life